Perception and Effectiveness of Online Anatomy Lab Exercise on Undergraduate Students of BPKIHS During COVID-19 Pandemic - Shah, Sandip; Koirala, Sarun; Rimal, Jyotsna; Khanal, Laxman; Mahat, Samyog (Nepal Journal of Health Sciences, 2024)
Introduction: Online mode of teaching learning activities were started for medical students of Nepal to reduce the risk of spreading virus during COVID-19 pandemic. BPKIHS started the modified online lab exercise (LABEX) for the undergraduate students after six months of pandemic. Objective: The main objective of study was to evaluate the student’s perception and effectiveness of modified online LABEX (prior content video uploading) during pandemic. Methods: The mixed method cross-sectional study design using semi-structured questionnaire was conducted. The questionnaire had sub-sections such as questions regarding students’ means of study, students’ perception on modified online lab exercise during pandemic and reflective writing. We collected the responses from 129 students after institutional ethical clearance and informed consent. Student’s paired test for analysis of effectiveness of modified online LABEX was done by using pre-test/post-test score. Thematic analysis was performed for reflective writing. A p<0.05 was considered as statistically significant. Results: The mean age was calculated as 20.84 year. The modified online LABEX increase the scoring of students for three consecutive sessions with an average score of 1.71; 1.55 & 1.09 respectively (p<0.001). We formulated 15 codes and 3 themes from reflective writing such as strength, weakness and recommendation of modified online LABEX. We found that “Accessibility of recorded Labex” (n=54) was major strength and “less efficient of online LABEX” (n=57) was major weakness. Conclusions: Although physical form of anatomy education is best way of learning but modified online LABEX can be used as alternative during pandemic like situations in future